Neonatal Sepsis in A Tertiary Care Hospital: Evaluation of Causative Agents and Antimicrobial Susceptibilities - Nahar, Begum Sharifun; Afroza, Syeda; Roy, Sunirmol; Nahar, Nurun; Kundu, Tarok Nath (Bangladesh Journal of Child Health, 2013)
Background: Neonatal sepsis is an important issue with a high morbidity and mortality rate in spite of new advances in antibiotic therapy. Identifying the causative agents and their antibiotic sensitivity in a neonatal care unit (NCU) helps the physician to choose the most appropriate antibiotic therapy. Objectives: This study was aimed to find out the etiological agent and antibiotic susceptibilities in newborn with culture positive sepsis. Methodology: This was a cross sectional study carried out in the neonatal care unit (NCU) of Sir Salimullah Medical College Mitford Hospital (SSMC) from June 2010 to May 2011. Seventy five neonates both preterm and term with culture proven sepsis were analyzed from admitted sick newborn to find out their etiology and antimicrobial sensitivity pattern. Blood culture was done in the department of Microbiology of the same medical college hospital. Results: In this study, out of 75 cases, early onset sepsis was observed in 55(73.33%) cases. Whereas late onset sepsis was in 20(26.66%) cases. Gram negative organisms were isolated in 59 (78%) of 75 cases. Pseudomonas aeroginosa 27 (46.55%), E Coli 15(25.86%) and Serratia 8 (13.79%) were the common microbes. Coagulase negative staphylococcus (CONS) was 10 (62%), followed by Staphylococcus aureus 6 (38%) were the major Gram positive isolates. Gram negative isolates were sensitive to Imipenem, Ceftazidime and Ciprofloxacin whereas 80 % gram positive isolates were sensitive to Amikacin. Conclusion : It was observed from this study that gram negative organisms like pseudomonas aeroginosa and E.coli were the common organisms for neonatal sepsis in hospitalized neonates and imipenem was the most sensitive drug against gram - ve septicaemia. DOI: http://dx.doi.org/10.3329/bjch.v37i1.15346 BANGLADESH J CHILD HEALTH 2013; VOL 37 (1) : 14-17